The effects of a weight belt on trunk and leg muscle activity and joint kinematics during the squat exercise - Zink, A. J.; Whiting, W. C.; Vincent, W. J; McLaine, A. J. (The Journal of Strength and Conditioning Research, 2001)
Fourteen healthy men participated in a study designed to examine the effects of weight-belt use on trunk- and leg-muscle myoelectric activity (EMG) and joint kinematics during the squat exercise. Each subject performed the parallel back squat exercise at a self-selected speed according to his own technique with 90% of his 1RM both without a weight belt (NWB) and with a weight belt (WB). Myoelectric activity of the right vastus lateralis, biceps femoris, adductor magnus, gluteus maximus, and erector spinae was recorded using surface electrodes. Subjects were videotaped from a sagittal plane view while standing on a force plate. WB trials were completed significantly faster (p < 0.05) than NWB trials over the entire movement and in both the downward phase (DP) and upward phase (UP). No significant differences in EMG were detected between conditions for any of the muscle groups or for any joint angular kinematic variables during either phase of the lift. The total distance traveled by the barbell both anteriorly and vertically was significantly greater (p < 0.01) in the WB condition than the NWB condition. The velocity of the barbell was significantly greater (p < 0.01) both vertically and horizontally during both the DP and UP in the WB condition as compared with the NWB condition. These data suggest that the use of a weight belt during the squat exercise may affect the path of the barbell and speed of the lift without altering myoelectric activity. This suggests that the use of a weight belt may improve a lifter's explosive power by increasing the speed of the movement without compromising the joint range of motion or overall lifting technique.